2014
DOI: 10.1007/s40271-014-0093-9
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Illness of Diabetic Peripheral Neuropathic Pain: A Qualitative Study

Abstract: DPNP is a significant complication of diabetes with multiple impacts for patient functioning and well-being, which increase the burden of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 35 publications
5
36
0
Order By: Relevance
“…Symptoms of DPNP can be continuous or intermittent [3,4] with patients reporting increased pain at night when tired or stressed [5]. Some patients report that DPNP and/or numbness fluctuates throughout the day or night (n = 26; 37 %), while for others pain and/or numbness are constant (n = 22; 31 %) [6]. Additional physical consequences of DPNP include loss of balance and coordination, which impairs gait and increases the risk of falls, and an inability to feel injury [3,4,7,8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Symptoms of DPNP can be continuous or intermittent [3,4] with patients reporting increased pain at night when tired or stressed [5]. Some patients report that DPNP and/or numbness fluctuates throughout the day or night (n = 26; 37 %), while for others pain and/or numbness are constant (n = 22; 31 %) [6]. Additional physical consequences of DPNP include loss of balance and coordination, which impairs gait and increases the risk of falls, and an inability to feel injury [3,4,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these physical impacts, several studies suggest that DPNP has negative impacts on quality of life physically (sleep, mobility, walking, energy, and vitality), overall perceptions of health, enjoyment of life, activities of daily life, employment, and recreational and social activities [1,3,[5][6][7][9][10][11][12][13][14][15][16][17][18][19][20]. Limited research suggests that these illness burdens may be experienced cross-culturally [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another aerobic exercise program lasting 16 weeks (n=14 patients) has shown significant improvement in decreasing general pain interference (walking, working, social relationship and sleep), however without changing pain intensity 15 . In line with these findings, a qualitative focus group study with 47 NP patients stresses the biopsychosocial complexity of their complaints, especially loss of functional capacity (walking, standing up, balance, orthostatism, mobility), decreased daily productivity (leisure activities, work), psychosocial consequences (anxiety, irritability, fear) and disorders (insomnia, non-restorative/regenerator sleep) 16 . Data such as these are consistent with reflections of studies with other chronic pain populations, where the pain relief objective does not overcome that of quality of life, quality of sleep and less interference of pain in daily life 17 .…”
Section: Introductionmentioning
confidence: 65%
“…With aerobic and resisted training during 10 weeks with 17 diabetic neuropathy patients, Kluding et al 14 have shown significant decrease in pain intensity measured by the visual analog scale (VAS) and decreased neuropathic symptoms, in addition to increased intraepidermal nervous fibers by skin biopsy. In spite of methodological limitations (e.g., small sample and lack of control group) this was one of the first studies to describe improved neuropathic symptoms and changes in skin nervous fibers after a program of exercises with NP diabetic patients 16 . Another aerobic exercise program lasting 16 weeks (n=14 patients) has shown significant improvement in decreasing general pain interference (walking, working, social relationship and sleep), however without changing pain intensity 15 .…”
Section: Introductionmentioning
confidence: 99%